Produtividade, severidade de mancha de alternaria e deficiência hídrica em diferentes épocas de semeadura do girassol em Santa Maria - RS - Guse, Fabrício Ivan (2009)
This study aimed to determine the occurrence of values of severity of injury caused by alternaria leaf spot and water deficit during the developmental cycle of three genotypes of sunflower and its relationship with meteorological conditions in seven sowing dates. In addition, aimed to quantify the final yield of grain and determine its relationship with water deficit and alternaria leaf spot severity for three sunflower genotypes grown in seven sowing dates. Rainfed experiments with three sunflower genotypes were conducted in Santa Maria nanthly planting dates from August 2007 to February 2008. Phenometric, phenological and alternaria leaf spot severity observations wise made. The soil water balance was calculated resulting in daily variation of water storage in the soil, the actual crop evapotranspiration and water deficit, based on data obtained with an automatic and a conventional weather stations. The highest values of final disease severity were observed in the sixth planting date for the three genotypes grown, indicating that the later the planting date the greater risk of alternaria leaf spot. There is a close relationship between days of healthy leaf area, area under the curve of progress of the disease, severity of observed final alternaria leaf spot and yield of achenes of sunflower. The highest yield for the three genotypes was obtained in the first two sowing dates and sowing after November should be availed in Santa Maria-RS.